Higher 5-HT1A Receptor Binding Potential During a Major Depressive Episode Predicts Poor Treatment Response: Preliminary Data from a Naturalistic Study - Parsey, Ramin V; Olvet, Doreen M; Oquendo, Maria A; Huang, Yung-yu; Ogden, R Todd; Mann, J John (Neuropsychopharmacology (New York, N.Y.), 2006)
Serotonin 1A (5-HT1A) binding potential (BP) as assessed by positron emission tomography (PET) is higher in major depressive disorder (MDD) in association with the higher expressing GG genotype of the 5-HT1A C-1019G polymorphism. We hypothesize that higher 5-HT1A BP and the GG genotype predict remission failure on antidepressant treatment. We determined 5-HT1A BP by PET and 5-HT1A C-1019G genotype in 43 controls and 22 medication-free MDD subjects. MDD was treated naturalistically and remission was defined as >50% reduction and a score of <or=10 on the 24 item Hamilton Scale 1 year after initiation of treatment after scanning. Despite equivalent treatment, nonremitters have higher pretreatment cortical BP and the GG genotype is over-represented compared with remitters. Higher 5-HT1A BP, perhaps due to greater gene expression, may predict antidepressant medication nonremission. The findings should be tested in a controlled prospective treatment study.